ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN CAPITAL STRUCTURE SEBAGAI VARIABEL MODERASI DAN FIRM SIZE, FIRM AGE, SALES GROWTH, SERTA PBV SEBAGAI VARIABEL KONTROL (Studi pada Perusahaan Non-finansial yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2022) - Ghofur, Azizul Mukminun; Hersugondo, Hersugondo (Diponegoro Journal of Management, 2023)
ABSTRACT The need for information to assess companies is very important for various parties in making decisions that related to the companies. Because of that, corporate governance has become one of indicators that provide information about quality of the governance of corporations that could be considerations for making decisions. The purpose of this research is to analysis the impact of corporate governance to firm financial performance that indicated by return on assets (ROA) then capital structure that indicated by debt to assets ratio (DAR. This research including population of non-financial companies that listed on Indonesia Stocks Exchange in 2018 – 2022. Purposive sampling is used as sampling technique for getting 71 non-financial companies that provide annual report in Indonesia Stocks Exchange website and provide Governance Disclosure Score at Bloomberg Terminal. Analysis method that used in processing data is panel data regression and moderated regression analysis (MRA) with E-views 12 as supported program. Result of this research shows that corporate governance positive and significantly influence firm financial performance measured by ROA also capital structure that measured by DAR could moderated the influence corporate governance to firm financial performance